PENGARUH VARIASI METODE DRILL DALAM MENINGKATAN KETERAMPILAN SHOOTING BOLA BASKET EKSTRAKULIKULER SMPN 2 CIASEM - Mursyidan, Ali; Iqbal, Rahmat; Fauzi Dermawan, Dikdik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of drill method variations on improving basketball shooting skills among extracurricular students at SMPN 2 Ciasem. The research employed an experimental method using a pre-test and post-test design. The sample consisted of 12 male students who were core players of the basketball team. The instrument used was a basketball shooting test adapted from the AAHPERD Basketball Skills Tests. The treatment was conducted over eight sessions within two weeks. Data analysis included normality testing, homogeneity testing, and paired sample t-test. The results showed that the mean pre-test score was 3.33, which increased to 5.58 in the post-test. The t-test results indicated a significance value of p < 0.05, meaning there was a significant difference between pre-test and post-test scores. Based on these findings, it can be concluded that variations of the drill method have a significant effect on improving basketball shooting skills. This method can be used as an effective learning approach to enhance shooting skills among junior high school students.